2012
DOI: 10.1080/00015458.2012.11680811
|View full text |Cite
|
Sign up to set email alerts
|

Early Low Volume Oral Synbiotic/Prebiotic Supplemented Enteral Stimulation of the Gut in Patients with Severe Acute Pancreatitis: A Prospective Feasibility Study

Abstract: Early low volume oral synbiotic/prebiotic supplemented enteral stimulation of the gut seems to be a potentially valuable complement to the routine treatment protocol of SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 1 publication
0
63
0
1
Order By: Relevance
“…Of the twelve articles, six were excluded: one was a retrospective study, three articles reported results of the same study, one article did not report the outcomes of mixed cohorts with severe and mild acute pancreatitis separately and, in one article, the experimental patients received probiotic-containing enteral nutrition (EN) and control patients received parenteral nutrition (PN) but not probiotic-free EN. Thus, six RCTs were ultimately included in our present systematic review [23-28]. The blinding, randomization, random sequence generation, withdrawals and dropouts, and allocation concealment for all the trials are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the twelve articles, six were excluded: one was a retrospective study, three articles reported results of the same study, one article did not report the outcomes of mixed cohorts with severe and mild acute pancreatitis separately and, in one article, the experimental patients received probiotic-containing enteral nutrition (EN) and control patients received parenteral nutrition (PN) but not probiotic-free EN. Thus, six RCTs were ultimately included in our present systematic review [23-28]. The blinding, randomization, random sequence generation, withdrawals and dropouts, and allocation concealment for all the trials are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest daily dose of probiotics was 3 × 10 7 bacteria, and the highest dose was 8 × 10 8 bacteria. The length of treatment was reported clearly in five studies, ranging from 7 to 28 days and not reported clearly in one study [28]. In three trials, the duration of treatment was 7 days [25-27], and the duration was 14 days in one study [24] and 28 days in one trial [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations